Genetic Modification of CD8+ T Cells to Express EGFR: Potential Application for Adoptive T Cell Therapies - Lozano, Teresa; Chocarro, Silvia; Martin, Celia; Lasarte-Cia, Aritz; del Valle, Cynthia; Gorraiz, Marta; Sarrión, Patricia; Ruiz de Galarreta, Marina; Lujambio, Amaia; Hervás-Stubbs, Sandra; Sarobe, Pablo; Casares, Noelia; et al. (Frontiers in Immunology, 2019)
Adoptive immunotherapy with ex vivo-expanded tumor-infiltrating lymphocytes (TILs) has achieved objective clinical responses in a significant number of patients with cancer. The failure of many patients to develop long-term tumor control may be, in part, due to exhaustion of transferred T cells in the presence of a hostile tumor microenvironment. In several tumor types, growth and survival of carcinoma cells appear to be sustained by a network of receptors/ligands of the ErbB family. We speculated that if transferred T cells could benefit from EGFR ligands produced by the tumor, they might proliferate better and exert their anti-tumor activities more efficiently. We found that CD8+ T cells transduced with a retrovirus to express EGFR responded to EGFR ligands activating the EGFR signaling pathway. These EGFR-expressing effector T cells proliferated better and produced more IFN-g and TNF-a in the presence of EGFR ligands produced by tumor cells in vitro. EGFR-expressing CD8 T cells from OT-1 mice were more efficient killing B16-OVA cells than control OT-1 CD8 T cells. Importantly, EGFR-expressing OT-1 T cells injected into B16-OVA tumor bearing mice were recruited into the tumor, expressed lower levels of the exhaustion markers PD1, TIGIT and LAG3, and were more efficient in delaying tumor growth. Our results suggest that genetic modification of CD8+ T cells to express EGFR might be considered in immunotherapeutic strategies based on adoptive transfer of anti-tumor T cells against cancers expressing EGFR ligands